Fabrication of high energy-density hybrid supercapacitors using electrospun V2O5 nanofibers with a self-supported carbon nanotube network - Chowdari, Bobba V. R. (2013)
A simple electrospinning technique is employed for the preparation of high-performance V2O5 nanofibers. The fibers thus prepared are subjected to heat treatment under the optimized conditions at 400 °C in air to achieve a single phase. The powder X-ray diffraction pattern confirms the formation of an orthorhombic structure with Pmmn space group. Morphological studies conducted by means of scanning electron microscopy (SEM) and transmission electron microscopy (TEM), clearly reveal the presence of a highly interconnected network of fibers with the diameter ranging from approximately 500–800 nm. After the heat treatment, translation of smooth fibrous morphology into porous fibers with embedded nanocrystals of V2O5 is noticed from the SEM measurements. The sintered V2O5 nanofibers are used to fabricate a hybrid electrochemical capacitor (HEC) and it is coupled with a substrate-free single-walled carbon nanotube (SWCNT) network (called “Bucky paper”) in a conventional organic electrolyte solution. Supercapacitive behavior of HEC is studied in both potentiostatic and galvanostatic modes at room temperature. The HEC demonstrated very stable and excellent cycling behavior during 3500 cycles of galvanostatic charge and discharge tests. This hybrid system is also well established during the rate capability studies from the applied current density of 30 to 210 mA g−1 and delivered maximum energy and power densities of 18 Wh kg−1 and 315 W kg−1, respectively.